Isolation of a myoglobin molten globule by selective cobalt(III)-induced unfolding - Blum, Ofer (The National Academy of Sciences, 1998)
Reaction of the Schiff-base complex [Co(acetylacetonate-ethylenediimine)(NH(3))(2)](+) with metmyoglobin at pH 6.5 yields a partially folded protein containing six Co(III) complexes. Although half of its α-helical secondary structure is retained, absorption and CD spectra indicate that the tertiary structure in both B-F and AGH domains is disrupted in the partially folded protein. In analogy to proton-induced unfolding, it is likely that the loss of tertiary structure is triggered by metal-ion binding to histidines. Cobalt(III)-induced unfolding of myoglobin is unique in its selectivity (other proteins are unaffected) and in allowing the isolation of the partially folded macromolecule (the protein does not refold or aggregate upon removal of free denaturant).